The co-occurrence of substance misuse, domestic abuse, and child maltreatment: Can Family Drug and Alcohol Courts play a part? - Harwin, Judith; Barlow, Charlotte (Frontiers in Psychiatry, 2022)
This review article focuses on the inter-relationship between substance misuse, domestic abuse and child maltreatment in the family justice system, especially in the context of care proceedings that determine whether a child can safely remain or return to their parents or needs a new permanent family. After considering the impact of domestic abuse and parental substance misuse on children, the review discusses the response of criminal and family law and treatment programmes in supporting families to address these problems holistically. Special attention is paid to the role of family drug and alcohol courts, an innovative approach to care proceedings, and their potential to provide a holistic treatment intervention when parental substance misuse and domestic abuse co-exist. Despite clear evidence of the greater harm to children when exposed to these two parental difficulties, the review has found a lack of systematic information on the prevalence of co-occurrence and a lack of effective integrated interventions. It concludes that FDACs offer a potential way forward within the court arena, but this is based on the conceptual model, given the absence of available empirical evidence. A particular focus of the review has been on efforts to overcome silos in practice and policy. The picture is mixed and there remain significant barriers to effectively align law, policy and practice to ensure that domestic abuse strategy recognises and responds to the overlaps and commonalities with substance misuse.